2021
DOI: 10.3390/nano11061370
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Quenching Effects on Growth Processes and Size Distributions of Silicon Nanoparticles at a Thermal Plasma Tail

Abstract: In this paper, quenching effects on silicon nanoparticle growth processes and size distributions at a typical range of cooling rates in a thermal plasma tail are investigated computationally. We used a nodal-type model that expresses a size distribution evolving temporally with simultaneous homogeneous nucleation, heterogeneous condensation, interparticle coagulation, and melting point depression. The numerically obtained size distributions exhibit similar size ranges and tendencies to those of experiment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Finally, the fast-cooled particles also appear more irregular with less well-defined edges on average, although this observation is mostly qualitative. This effect has previously been observed in uranium, iron, and aluminum oxides synthesized in the PFR as well as in ICP-synthesized alumina and thermal plasma-made silicon nanoparticles . These results in conjunction with our own suggest that gentler temperature histories lead to more uniform and well-defined particle morphologies, while rapid temperature drop-offs such as those induced under fast cooling give rise to irregular particles.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the fast-cooled particles also appear more irregular with less well-defined edges on average, although this observation is mostly qualitative. This effect has previously been observed in uranium, iron, and aluminum oxides synthesized in the PFR as well as in ICP-synthesized alumina and thermal plasma-made silicon nanoparticles . These results in conjunction with our own suggest that gentler temperature histories lead to more uniform and well-defined particle morphologies, while rapid temperature drop-offs such as those induced under fast cooling give rise to irregular particles.…”
Section: Discussionmentioning
confidence: 99%
“…The control of the plasma jet parameters is especially important at the stage of evaporation/dissociation of the precursor (in the form of a powder or gas) during the synthesis of nanoparticles [12]. It is known that, in the general case, the transfer channels of the gaseous and solid phases in two-phase flows of such processes do not coincide.…”
Section: Research Resultsmentioning
confidence: 99%
“…The problem of the LIB development as a whole is defined [3,4]. As for the technological features of the plasma, in [11,12], using the computational method, 3D modeling was performed depending on the time of the plasma jet. It is shown that when a uniform magnetic field is applied due to the Lorentz and Joule heating forces, the flow is laminarized, the plasma jet is elongated, and the temperature profile becomes more filled.…”
Section: Research Of Existing Solutions To the Problemmentioning
confidence: 99%
“…The crucial issue of this approach is the production of high-quality inks, in which Si NPs with a uniform size and shape are dispersed without agglomeration. Si NP inks satisfying these requirements had been hard to be produced by conventional processes such as plasma synthesis, chemical vapor deposition, , laser ablation, ,, and mechanical milling. , In previous work, ,, we developed a process to produce suspensions of almost perfectly spherical Si NPs [Si nanospheres (Si NSs)] with very narrow size distributions. The suspension exhibited size-dependent vivid structural color due to the Mie resonance. ,, By mixing the suspension with an optically transparent binder such as polyvinylpyrrolidone, we produced the structural color inks and demonstrated coloration of a base material such as a PET film by painting …”
Section: Introductionmentioning
confidence: 99%